Comparative Testing between Electrical Impedance and Hybrid Nuclear Devices for Measuring Moisture and Density in Soils. Issue 1 (January 2017) - Berney, Ernest S.; Mejías-Santiago, Mariely
The U.S. Army Engineer Research and Development Center validated the effectiveness of the TransTech Combined Asphalt Soil Evaluator (CASE) electrical impedance gauge and the Troxler eGauge hybrid electric-nuclear gauge as suitable replacements for nuclear density gauge (NDG) technology. Comparisons of soil density and moisture content were made between the gauges for six distinct soil types at varying densities and levels of moisture content. The CASE unit was calibrated using the sand cone and hot-plate moisture content prior to its correlation to the NDG; the eGauge was used in its shipped configuration without calibration. Full-scale test sections ranging from crushed limestone to fat clays were constructed for the soil evaluations. Results indicated that wet and dry densities obtained with the eGauge very closely matched those of the NDG, with a coefficient of determination (R 2 ) of approximately 94%, but with an R 2 of 85% for the measured moisture contents. The calibrated CASE unit's comparison with the NDG moisture content was excellent, with an R 2 of 98%, but the R 2 values were much lower than those of the eGauge for its dry and wet density, at 83% and 59%, respectively. Further, an average R 2 of only 30% was found for the CASE unit's ability to capture changing wet density during construction operations, versus 80% for the eGauge. On the basis of the Engineer Research and Development Center findings, the eGauge is recommended as the better replacement for the NDG for wet or dry density measurements. It also requires little to no calibration and has no transport or licensing restrictions.